Leptin revisited: The role of leptin in starvation. (3rd September 2018) - Perry, Rachel J.
ABSTRACT: Starvation causes reductions in plasma leptin concentrations, but the physiologic impact of this observation had not been documented in the starved state. Here we discuss our recent work demonstrating that hypoleptinemia activates the hypothalamic-pituitary-adrenal (HPA) axis, increasing white adipose tissue (WAT) lipolysis and mediating a shift from glucose to fat metabolism to maintain euglycemia in fasted rats.